Aplikasi Sistem Pakar untuk Mendiagnosa Kerusakan Monitor CRT - Abid Yanuar Badharudin; Dwi Aryanto (JUITA : Jurnal Informatika, 2011)
This research aims to design up a program of expert system to diagnose the damage of CRT monitor (Cathode Ray Tube) with a solution of repair. This system using knowledge base rules and decision table as its knowledge representation. The programming language in use is Visual Basic 6.0. Research results is a system with consulting, addition of a base rule, and increased knowledge menus. This expert system application is able to diagnose damage to CRT monitor also provides solutions in fixes